2016
DOI: 10.1111/hdi.12521
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms among patients receiving in‐center hemodialysis: A qualitative study

Abstract: Introduction Assessment of dialysis-related symptoms is not currently a requirement for hemodialysis (HD) providers in the United States. The purpose of this study was to describe patients' perspectives on symptoms associated with end-stage chronic kidney disease treated with thrice-weekly, in-center HD. Methods We performed a qualitative study using interpretive description. Interview questions were based on a KDIGO (Kidney Disease Improving Global Outcomes) controversies conference and a literature review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
51
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 35 publications
5
51
0
3
Order By: Relevance
“…Consistent with prior reports, participants desired more interaction with their providers around symptoms. [5, 6] Many participants indicated that SMaRRT-HD™ responses would be useful for their care teams. For instance, in clinical practice, this PROM may facilitate conversations about symptoms between patients and dialysis care technicians, nurses, and medical providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with prior reports, participants desired more interaction with their providers around symptoms. [5, 6] Many participants indicated that SMaRRT-HD™ responses would be useful for their care teams. For instance, in clinical practice, this PROM may facilitate conversations about symptoms between patients and dialysis care technicians, nurses, and medical providers.…”
Section: Discussionmentioning
confidence: 99%
“…[2, 4] Recent studies have found that patients receiving hemodialysis desire greater interaction with their health care providers about symptoms. [5, 6] Patients, along with other dialysis stakeholders, have identified symptom relief as a top priority and called for increased symptom focus in both research and clinical practice. [7, 8]…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Qualitative data suggest that suboptimal BP and volume management negatively affect quality of life. [7][8][9] Efforts to develop consensus best practices in managing BP and volume in dialysis have been hampered by an absence of widely available, accurate, and objective measures of extracellular volume status, as well as a lack of high-quality evidence. As such, related practice patterns vary considerably, both within local communities and throughout the world.…”
mentioning
confidence: 99%
“…13 The quality of life of patients on HD is significantly affected as they are in distress for feeling constantly thirsty and not being allowed to drink fluids. 9,10 Although thirst has a subjective facet, scales have been used to diagnose and assess the thirst of patients on HD in terms of intensity (visual analogue scale -VAS), 14 frequency (Dialysis Thirst Inventory -DTI), 15 and distress (Thirst Distress Scale -TDS). 16,17 The TDS is the only scale adapted and validated in other countries, including Turkey, 18 Japan, 19 Sweden, 19 the Netherlands, 19 and Italy.…”
Section: Introductionmentioning
confidence: 99%